α-Arbutin ameliorates UVA-induced photoaging through regulation of the SIRT3/PGC-1α pathway - Lu, Fang; Zhou, Qi; Liang, Mengdi; Liang, Huicong; Yu, Yiwei; Li, Yang; Zhang, Yan; Lu, Ling; Zheng, Yan; Hao, Jiejie; Shu, Peng; Liu, Jiankang (Frontiers in Pharmacology, 2024)
Owing to its tyrosinase inhibitory activity, α-arbutin has been added to several skin care products as a skin-lightening agent. However, the protective effect of α-arbutin against ultraviolet A (UVA)-induced photoaging has not been well investigated. The present study was designed to investigate the photoprotective effect and mechanism of α-arbutin against UVA-induced photoaging. In in vitro experiments, HaCaT cells were treated with UVA at a dose of 3 J/cm 2 to evaluate the anti-photoaging effect of α-arbutin. α-Arbutin was found to exhibit a strong antioxidant effect by increasing glutathione (GSH) level and inhibiting reactive oxygen species (ROS) production. Meanwhile, α-arbutin markedly improved the expression of sirtuin 3 (SIRT3) and peroxisome proliferator-activated receptor γ coactivator 1 α (PGC-1α) proteins, initiating downstream signaling to increase mitochondrial membrane potential and mediate mitochondrial biogenesis, and improve mitochondrial structure significantly. In in vivo analysis, the mice with shaved back hair were irradiated with a cumulative UVA dose of 10 J/cm 2 and a cumulative ultraviolet B (UVB) dose of 0.63 J/cm 2 . The animal experiments demonstrated that α-arbutin increased the expression of SIRT3 and PGC-1α proteins in the back skin of mice, thereby reducing UV-induced skin damage. In conclusion, α-arbutin protects HaCaT cells and mice from UVA damage by regulating SIRT3/PGC-1α signaling pathway.